The view of the coronavirus pandemic response through the lens of political philosophy: Utilitarianism and the Rawlsian approach - Fusiek, Dawid Aristotelis (HAPSc Policy Briefs Series, 2020)
The paper discusses the moral justification of the adoption of the restriction measures during the coronavirus pandemic, and attempts to connect it with the notion of human rights and freedom. The popular Western response falls in the line of the work of John Rawls and his perception of justice and fairness. The premise of Rawlsian approach is that the state has a duty to protect everyone as they themselves would wish to be protected. However, as the time has progressed, the outcomes of the lockdown has begun to become visible, hence challenging the initial Rawlsian view of the issue at stake. Under the new circumstances, the political theory of utilitarianism seems to be gaining ground, but in its most brutal form. Dismissing the roots of the utilitarian theory, the utilitarian calculus has been used as a sophism by politicians for the introduction of the notion of “sacrifice” for the greater good. By the presentation and application of the two approaches, in the face of a future reemergence of similar problem, this paper argues for the adoption of a combining approach that covers the concerns of both and answers the moral dilemmas that have emerged from this period of quarantine.